Renewed occurrence of schooling scalloped hammerhead (Sphyrna lewini) and of great hammerhead (S. mokarran) sharks in the Cayman Islands - Gore, Mauvis; Kohler, Johanna; Ormond, Rupert; Gallagher, Austin; Fernandes, Teresa; Austin, Timothy; Pattengill-Semmens, Christy (Frontiers in Marine Science, 2024)
The scalloped hammerhead shark (Sphyrna lewini), a critically endangered species with a decreasing global population, is characterised by its occurrence in large schools. Such schools are still observed today in the Pacific Ocean, but this is generally not the case in the Atlantic Ocean, and in the Cayman Islands not since the 1970s. Here we report a recent record of a school of S. lewini in deep water off Grand Cayman, and describe a recent, concomitant increase in numbers of the species, and its critically endangered congener, the great hammerhead (Sphyrna mokarran), around the Cayman Islands. Relative population trends and seasonal patterns were assessed using data from shallow and deep-water BRUVS, scientific longlining, citizen science projects including the Sharklogger Network and REEF, and social media reports. It appears that S. lewini may be slowly re-occupying the area, selecting and using deeper waters to school, while S. mokarran has also become less scarce than hitherto.